Kebijakan Penerimaan PPPK Guru dan Dampak terhadap Pendidikan Swasta - Damanik, Nuraini Karim; Ariyanto, Avif; Setiawan, Farid (Lembaga Yasin AlSys, 2022)
Starting in 2021, the government will stop recruiting Civil Servant Candidates from the teacher formation, replacing it with a government employee line with a work agreement (PPK). This study also aims to analyze the policy of terminating PNS teachers. side of mistakes in policy making so as to make actions that are detrimental to private schools as a result of taking teachers and transferring to other schools. UU no. 14 of 2005 concerning Teachers and Lecturers states that teachers are professional educators, where teachers have a minimum educational qualification of a bachelor's degree (S1) and are certified. In practice, education still relies on honorary teachers because of the shortage of professional educators. In terms of qualifications and competence, only a small proportion of honorary teachers have an undergraduate education and are certified. There are still many teacher qualifications that have not been mapped, especially auxiliary teachers who have not been registered in the basic education data. This paper examines the scheme of Government Employees with Work Agreements (PPPK) in meeting the shortage of educators in schools. The open selection of PPPK for honorary teachers and graduates of Teacher Professional Education (PPG) can be a solution for improving the governance of educators. This step is expected to overcome the problem of the shortage of competent educators and teachers can concentrate fully on carrying out their educational tasks without worrying about their welfare. Synergy between ministries/institutions and all related parties, including Commission X of the DPR RI through the functions of legislation, budgeting, and supervision is needed so that the PPPK selection produces quality teachers.